2023
DOI: 10.1101/2023.01.15.524087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dally is not essential for Dpp spreading or internalization but for Dpp stability by antagonizing Tkv-mediated Dpp internalization

Abstract: Dpp/BMP acts as a morphogen to provide positional information in the Drosophila wing disc. Key cell-surface molecules to control Dpp morphogen gradient and signaling are heparan sulfate proteoglycans (HSPGs). In the wing discs, two HSPGs, the glypicans Division abnormally delayed (Dally) and Dally-like (Dlp) have been suggested to act redundantly to control these processes through direct interaction of their heparan sulfate (HS) chains with Dpp. Based on this assumption, a number of models on how glypicans con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Unlike the GFP-dpp allele, the two newly generated alleles were not haploinsufficient but semi-lethal. To overcome the partial embryonic lethality, we introduced a transgene called “JAX”, which contains the genomic region of dpp critical for the early embryogenesis 29 but does not rescue the wing phenotypes of dpp mutants 20 . We found that JAX greatly rescued the lethality of each allele and each allele becomes easily homozygous viable without obvious phenotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike the GFP-dpp allele, the two newly generated alleles were not haploinsufficient but semi-lethal. To overcome the partial embryonic lethality, we introduced a transgene called “JAX”, which contains the genomic region of dpp critical for the early embryogenesis 29 but does not rescue the wing phenotypes of dpp mutants 20 . We found that JAX greatly rescued the lethality of each allele and each allele becomes easily homozygous viable without obvious phenotypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Endocytic trafficking has been proposed to regulate extracellular Dpp gradient formation through transcytosis 16 , recycling 17 , or a sink 20-22 . We found that extracellular Dpp distribution expands upon blocking early endocytosis but is not largely affected upon blocking the following endocytic trafficking such as MVBs formation, late endosome, or recycling, supporting that early endocytosis simply acts as a sink for Dpp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the Dpp gradient scales with tissue size [ 116 , 120 ]. To fulfil this job, there is a mechanism which tunes the during organ growth, keeping the gradient and tissue proportional [ 87 , 88 , 116 , 125 , 126 , 127 ]. In this particular organ (i.e., wing), Dpp signalling scaling failure leads to defects in tissue size and pattern formation [ 87 , 88 , 116 , 126 , 128 , 129 ].…”
Section: Scaling Phenomena During Development Adulthood and Tumorigen...mentioning
confidence: 99%